EFEKTIVITAS PEMANFAATAN FASILITAS KAWASAN BERIKAT OLEH INDUSTRI TERTENTU DI KPP PRATAMA KARAWANG SELATAN: STUDI KASUS INDUSTRI SUKU CADANG DAN AKSESORIS KENDARAAN BERMOTOR RODA EMPAT ATAU LEBIH - Ardiansyah, Benny Gunawan (Simposium Nasional Keuangan Negara, 2020)
After running for 30 years, the taxation facilities for companies in the bonded zones raise questions, especially related to effectiveness. Effectiveness could be measured with the level of utilization and usefulness, as measured by profitability. This study utilized statistical data analysis and shrewdness of financial statement analysis. The results of the analysis show that the facilities in the Bonded Zone are proven to have not been utilized accordingly. Meanwhile, the level of profitability is also quite low, which shows that the company's performance based on financial reporting is still difficult to compete